Analisis Pengaruh Kinerja Keuangan & Faktor Makroekonomi terhadap Harga Saham Perusahaan Hotel, Restoran dan Pariwisata Pada ISSI - Sahroni, Putri Rizki; Setiawan, Iwan; Purbayati, Radia; Ruhana, Nafisah (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study is to find out how the effect of ROA, DER, EPS, inflation, exchange rates and interest rates on hotel, restaurant and tourism company stock prices on the Indonesian Sharia Stock Index (ISSI) for 2018 – 2021. Descriptive-quantitative method with data analysis panel is the method to be used in this study. This study utilizes real-time data from the Indonesia Stock Exchange (IDX), the Central Bureau of Statistics (BPS) and Bank Indonesia (BI). In this study, there were 17 companies that successfully met the sampling criteria using purposive sampling method. The study findings show that ROA has a positive effect and DER has a negative effect on stock prices, while EPS, inflation, exchange rates and interest rates have no effect on stock prices.